Nilai Persentase Penutupan Vegetasi Sub DAS Rokan Kiri AWLR Lubuk Bendahara Tahun 2021 - Ilham Burhanudin; Yohanna Lilis Handayani; Trimaijon (Jurnal Teknologi dan Rekayasa Sipil, 2022)
The Rokan Kiri sub-watershed has experienced the development of land use from forests to plantations, agriculture and settlements. Changes in land use can result in floods and cause water availability to decrease every year. The decrease in water availability is due to the ability of the sub-watershed to respond to falling rain. The purpose of this study was to analyze Persentage of Vegetation Cover (PPV) in the Rokan Kiri sub-watershed AWLR Station of Lubuk Bendahara in 2021. The analysis of land use types was taken by digitizing the Landsat 8 image map in 2021 with the Arcmap application.. Based on the results of the study, it was found that the Rokan Kiri AWLR Lubuk Bendahara sub[1]watershed has a forest area of 1,312.81 km², shrubs and plantations area of 1,635.95 km², agricultural land area of 86.27 km², open land area of 41.15 km² , the built up land area is 17.09 km², and the water area is 31.57 km². The results obtained indicate that the Rokan Kiri sub-watershed at the Lubuk Bendahara AWLR station has a PPV value of 94.37% and is still in the "very good" category, because the PPV value of research obtained is more than 80%.